Turning the tide of male juvenile delinquency: the Ocean Tides approach - Grebstein, Lawrence C. (Springer Publ. Company, 2016)
Preface -- Contributions to the literature -- Practical tips for practitioners -- A synopsis of what follows -- Acknowledgments -- Ocean tides rising : history -- Currents : who the boys are -- Explaining the Ocean's Tides : theory -- An undertow : personal child abuse victimization and exposure to parental interpersonal violence (PIPV) -- Charting a course : the program at ocean tides -- Calming seas : managing the Ocean Tides residents -- Navigating the waters : the role of the clinical psychologist as a consultant -- At the helm : interviewing adolescent male juvenile delinquents -- Stem the tide : case histories -- Sailing home : final thoughts